PEMANFAATAN BOTOL BEKAS UNTUK TANAMAN HIDROPONIK SAYURAN SISTEM WICK UNTUK MENANGGULANGI SAMPAH BOTOL BEKAS DAN MENAMBAH PENGHASILAN RUMAH TANGGA OLEH MAHASISWA KKN DESA MAREDAN BARAT - Irda Sayuti; Yola Aprila; Angga Irama; Alfirahmani, Alfirahmani; Yollanda Susilawati; Marni Srihartati Harefa; Nuur Badriyyah Akmal; Tedy Akmal Hernando; Dian Astri Maulani; Gusti Ajeng Ayuni; et al. (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Hydroponics is a way of growing plants with flowing water without using soil media, but instead of soil using media such as rockwool, rice husks, cotton, etc., where hydroponic plants are more concerned with using nutrients dissolved in water. In addition, hydroponics also does not require a large area of ​​land as a place to grow crops, making it easier for housewives in Maredan Barat Village to increase their food needs. In this service activity, counseling and demonstrations were carried out on how to grow wick system hydroponic plants with KIT and with alternative materials such as used bottles, as well as making hydroponic plants on herbal plant land belonging to the Maredan Barat Village Office, Kec. Tualang, Kab. Siak, Riau. The purpose of this counseling and demonstration is hopefully it can be used as an example and used by the community in the future after the KKN team is finished in service